2018
DOI: 10.1177/1098300718766657
|View full text |Cite
|
Sign up to set email alerts
|

Evidence Review for Teacher Praise to Improve Students’ Classroom Behavior

Abstract: In this study, a systematic review was conducted to examine the evidence base for teacher praise for students without severe disabilities in K-12 classroom settings. Specifically, reviewers followed standards presented by the Council for Exceptional Children and the What Works Clearinghouse to evaluate the methodological quality of 30 studies meeting inclusion criteria. Only 11 studies were rated as being methodologically sound. The review team then classified effects of the 11 methodologically sound studies a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 52 publications
(68 reference statements)
0
39
0
Order By: Relevance
“…In general, research indicates BSP is an effective and efficient strategy to facilitate behavior change in students (Moore et al, 2019). However, a tool for measuring functional and topographical characteristics (i.e., specificity, contingency, variety) of praise is needed to examine the affect various praise characteristics have on student behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, research indicates BSP is an effective and efficient strategy to facilitate behavior change in students (Moore et al, 2019). However, a tool for measuring functional and topographical characteristics (i.e., specificity, contingency, variety) of praise is needed to examine the affect various praise characteristics have on student behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have studied the effects of praise on students with disabilities for decades (e.g., Gable & Shores, 1980; Hall et al, 1968; Markelz et al, 2019; Sutherland et al, 2000). Unfortunately, the long history of praise research limits the methodological quality of many studies included in systematic reviews to determine whether teacher praise is an evidence-based practice (Moore et al, 2019). However, empirical evidence repeatedly demonstrates positive effects of praise on a range of academic and behavioral outcomes, including increased student time on task, decreased inappropriate behaviors, and reduced student tardiness (Royer et al, 2019).…”
mentioning
confidence: 99%
“…Reviewers may also choose to assess the rigor of included studies without using quality as a basis for exclusion. However, critical differences in available quality indicators may produce contradictory findings in reviews addressing the same topic (Moore et al, 2018; Wendt & Miller, 2012). O’Keeffe et al (2012) documented the vacillating conclusions regarding the efficacy of repeated reading, an intervention designed to improve reading fluency, across multiple reviews and meta-analyses.…”
Section: Bias In Systematic Literature Reviewsmentioning
confidence: 99%
“…The positive effects of BSP on secondary students' AEB are consistent with Blaze et al's (2014) findings, and the positive effects of BSP on secondary students' DB are consistent with findings from both Blaze et al and Haydon and Musti‐Rao (2011). These results add to the BSP literature as few studies have evaluated the independent effects of BSP in secondary classrooms while also demonstrating treatment effects with at least three classrooms (Moore et al, 2019; Royer et al, 2019).…”
Section: Discussionmentioning
confidence: 55%
“…Specifically, the results of two recent systematic reviews of the praise literature found few studies directly evaluating the independent effects of BSP on the behavior of secondary students at the classroom level (Moore et al, 2019; Royer, Lane, Dunlap, & Ennis, 2019). Many studies evaluating BSP in secondary classrooms have either combined BSP with other intervention components (Hollingshead, Kroeger, Altus, & Trytten, 2016; Houghton, Wheldall, Jukes, & Sharpe, 1990; McAllister et al, 1969; Pisacreta, Tincani, Connell, & Axelrod, 2011), or specifically evaluated training packages for increasing teachers' BSP and were unable to demonstrate functional relations between BSP and student behaviors (Duchaine, Jolivette, & Fredrick, 2011).…”
Section: Behavior‐specific Praisementioning
confidence: 99%